2019
DOI: 10.3390/brainsci9060134
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Trigeminal Neuralgia: A Comparison of Dose Protocols

Abstract: Purpose: A variety of treatment plans including an array of prescription doses have been used in radiosurgery treatment of trigeminal neuralgia (TN). However, despite a considerable experience in the radiosurgical treatment of TN, an ideal prescription dose that balances facial dysesthesia risk with pain relief durability has not been determined. Methods and Materials: This retrospective study of patients treated with radiosurgery for typical TN evaluates two treatment doses in relation to outcomes of pain fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Typical TN causes severe and sudden volleys of shock-like facial pain that lasts a few seconds to a few minutes in the distribution of one or more divisions of the trigeminal nerve. 1 Medication therapy is nearly always introduced as the primary treatment. However, they may be associated with side effects or unable to control the pain.…”
Section: Introductionmentioning
confidence: 99%
“…Typical TN causes severe and sudden volleys of shock-like facial pain that lasts a few seconds to a few minutes in the distribution of one or more divisions of the trigeminal nerve. 1 Medication therapy is nearly always introduced as the primary treatment. However, they may be associated with side effects or unable to control the pain.…”
Section: Introductionmentioning
confidence: 99%
“…Trigeminal neuralgia is a severe and disabling face pain that can be effectively treated surgically in most people when medicines fail. Boling et al reported their experience with different radiosurgery dosing protocols to target the root entry zone of the trigeminal nerve in the treatment of medically intractable trigeminal neuralgia [4]. The authors found that a higher dose regimen of 85Gy was the most effective and durable treatment for the facial pain.…”
mentioning
confidence: 99%